Patient Perspectives on Peer Mentoring: Type 1 Diabetes Management in Adolescents and Young Adults. (February 2015) - Lu, Yang; Pyatak, Elizabeth A.; Peters, Anne L.; Wood, Jamie R.; Kipke, Michele; Cohen, Marisa; Sequeira, Paola A.
Purpose: The purpose of the study was to identify attitudes and topics relevant to peer mentoring as an adherence-promoting intervention for adolescents and young adults (YAs) with type 1 diabetes (T1D). Methods: Self-administered survey data were collected in 2 diabetes clinics from a convenience sample of adolescents as prospective mentees (ages 13-18) and YAs as prospective mentors (ages 19-25) with T1D. Survey topics included demographics, disease history, glycemic control, adherence, depression, barriers to disease management, social support, and interest in peer mentoring. Descriptive statistical analyses, thematic coding, and stepwise multivariate logistic regression were performed. Results: A majority of the 54 adolescents and 46 YAs expressed interest in a peer mentoring program. Having supportive friends and living in a large household positively predicted adolescent interest in having a peer mentor. Approximately one-third of all participants experienced social barriers to diabetes management. For adolescents, barriers included inflexible schedules, unfamiliar foods, and the embarrassment of checking blood glucose in front of others. Young adults reported barriers in tracking food consumption and remembering to check blood glucose. Various diabetes management skills were in high demand by adolescents, who especially desired to learn about managing T1D on their own and in college. Participants were open to multiple communication modes, including in-person meetings, phone, text messaging, and social media. Conclusions: Many adolescents and young adults with T1D are interested in peer mentoring as a way to facilitate learning and sharing essential diabetes management skills and experiences.